Pengaruh Pengelolaan Keuangan, Pemahaman Sistem Akuntansi Dan Kompetensi Sumber Daya Manusia Terhadap Kinerja Badan Usaha Milik Desa (BUMDesa) Di Kecamatan Gianyar Kabupaten Gianyar - SANG AYU MADE ARIMAS PUTRI; Ni Putu Ayu Kusumawati; I Wayan Budi Satriya (UNHI Press, 2026)
The goal of this study is to look at how Financial Management, knowledge of Accounting Systems, and the skills of Human Resources affect the performance of Village-Owned enterprises. Enterprises (BUMDesa) in Gianyar District, Gianyar Regency. In 2024, Gianyar District will be the region with the largest number of BUMDesa in the advanced and developing categories in Gianyar Regency. However, several BUMDesa still face challenges such as a lack of competent human resources in management, especially in terms of financial management, understanding of accounting systems and some BUMDesa actors who have less than optimal work quality. The population of this study includes all employees, advisors, and BUMDesa supervisors in Gianyar district. A total of 79 samples were selected using the purposive sampling method, which results in a population of 99. The study's results indicate that BUMDesa performance is greatly enhanced through effective financial management and a good understanding of the accounting system.,and human resource competencies.